5th International Symposium on Tonal Aspects of Languages (TAL 2016) 2016
DOI: 10.21437/tal.2016-25
|View full text |Cite
|
Sign up to set email alerts
|

Complete and incomplete neutralisation in Fuzhou tone sandhi

Abstract: This is a study of incomplete neutralisation using Fuzhou tone sandhi as a test case. In Fuzhou Min, Tone 44 and Tone 232 undergo putative neutralisation into Tone 53 preceding a set of low tones, while T44 and T53 are neutralised into T44 preceding T53. Data from 10 Fuzhou speakers show the former neutralisation to be acoustically incomplete, with the sandhi tone of underlying Tone 44 having a higher pitch onset, while the latter appears to be acoustically complete. This result expands the typology of incompl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…Carryover effects have been found largely assimilatory, whereas anticipatory effects tend to be dissimilatory. Such is the case for Mandarin, Cantonese, Yoruba (Laniran & Clements, 2003), Thai, Fuzhou Min (Li, 2015), Tianjin Chinese, Taiwanese, and Itunyoso Trique (DiCanio, 2012;DiCanio & Nam, 2013). Still other studies found that carryover effects are not predominantly assimilatory, and anticipatory effects are not limited to dissimilation, as shown in Malaysian Hokkien (Chang & Hsieh, 2012), Vietnamese (Brunelle, 2009), Nanjing Chinese (Chen et al, 2018), and Mizo (Sarmah et al, 2015).…”
Section: Tone and Phonation Coarticulationmentioning
confidence: 93%
“…Carryover effects have been found largely assimilatory, whereas anticipatory effects tend to be dissimilatory. Such is the case for Mandarin, Cantonese, Yoruba (Laniran & Clements, 2003), Thai, Fuzhou Min (Li, 2015), Tianjin Chinese, Taiwanese, and Itunyoso Trique (DiCanio, 2012;DiCanio & Nam, 2013). Still other studies found that carryover effects are not predominantly assimilatory, and anticipatory effects are not limited to dissimilation, as shown in Malaysian Hokkien (Chang & Hsieh, 2012), Vietnamese (Brunelle, 2009), Nanjing Chinese (Chen et al, 2018), and Mizo (Sarmah et al, 2015).…”
Section: Tone and Phonation Coarticulationmentioning
confidence: 93%
“…Incomplete neutralization is not limited to the process of final devoicing as the following processes have also been documented as being incomplete: tapping/flapping in American English (Fox & Terbeek, 1977;Herd et al, 2010;Braver, 2014), intrusive stops in English (Fourakis & Port, 1986), schwa epenthesis in English (Davidson, 2006), coda aspiration in Andalusian Spanish (Gerfen, 2002;Bishop, 2007), coda liquids in Puerto Rican Spanish (Simonet et al, 2008;Beaton, 2016), French schwa deletion (Fougeron & Steriade, 1997), Russian voicing assimilation (Burton & Robblee, 1997), epenthesis in Lebanese Arabic (Gouskova & Hall, 2009), tone sandhi in Cantonese (Yu, 2007), Mandarin (Peng, 2000) and Fuzhou (Li, 2016), Japanese monomoraic lengthening (Braver & Kawahara, 2016), and word-final lenition in Chilean Spanish (Bolyanatz, 2020). Durational cues appear to be the majority of what is presented as being incomplete, but there is not enough evidence to suggest it is limited to the temporal domain as in some cases it was exclusively nondurational cues which were found to be incomplete (Burton & Robblee, 1997;Yu, 2007).…”
Section: Incomplete Neutralizationmentioning
confidence: 99%